Harmonizing Molina's rejection of transworld damnation with Craig's solution to the problem of the unevangelized - MacGregor, Kirk R. (International journal for philosophy of religion, 2018)
Recent scholarship has demonstrated Molina's rejection of transworld damnation, claiming instead that there is at least one feasible world where any individual is freely saved, lost, or does not exist. This article argues that one can subscribe to Molina's doctrine of individual predestination while maintaining, with William Lane Craig, that no actual person who fails to hear the gospel and is lost would have been saved in some feasible world where s/he heard the gospel. As part of the divine deliberation, God could narrow down the spectrum of feasible worlds to a lower-order spectrum by factoring out worlds which, among other conditions, contain anyone who does not fall into either of two types. The first type comprises persons saved in at least one world where they receive only general revelation at the moment of salvation, lost in at least one world where they receive only general revelation, and lost in every world where they receive special revelation without first appropriating salvation through general revelation. The second type comprises persons saved in at least one world where they receive special revelation without first appropriating salvation through general revelation and lost in at least one comparable world.